2015
DOI: 10.1002/jssc.201500237
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous extraction and quantification of lamotrigine, phenobarbital, and phenytoin in human plasma and urine samples using solidified floating organic drop microextraction and high‐performance liquid chromatography

Abstract: A novel and simple method based on solidified floating organic drop microextraction followed by high-performance liquid chromatography with ultraviolet detection has been developed for simultaneous preconcentration and determination of phenobarbital, lamotrigine, and phenytoin in human plasma and urine samples. Factors affecting microextraction efficiency such as the type and volume of the extraction solvent, sample pH, extraction time, stirring rate, extraction temperature, ionic strength, and sample volume w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Several analytical methods such as HPLC (Ferreira et al, 2014;Romanyshyn et al, 1994;Asadi et al, 2015), LC-MS (Karinen et al, 2015;Hori et al, 2006;Hoshina et al, 2009;Qu et al, 2016), and GC (Roveri, Paranhos, Yonamine, 2016;Menck de Almeida et al, 2012;Queiroz et al, 2002) were reported in literature for determining phenobarbital in different biological samples. Some of the utilized instruments such as LC-MS and LC-MS/MS are expensive and unavailable for analysis of biological samples in routine laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Several analytical methods such as HPLC (Ferreira et al, 2014;Romanyshyn et al, 1994;Asadi et al, 2015), LC-MS (Karinen et al, 2015;Hori et al, 2006;Hoshina et al, 2009;Qu et al, 2016), and GC (Roveri, Paranhos, Yonamine, 2016;Menck de Almeida et al, 2012;Queiroz et al, 2002) were reported in literature for determining phenobarbital in different biological samples. Some of the utilized instruments such as LC-MS and LC-MS/MS are expensive and unavailable for analysis of biological samples in routine laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical methods for determination of AEDs, including PHT, have been reviewed in a previous articles [4]. PHT alone and PHT in combination with other AEDs have been determined using a number of analytical techniques including colorimetric [5], spectrophotometric [6,7], immunoassay [8–10], HPLC‐UV [11–19], LC–MS/MS [20–22], GC with a thermionic specific detector (GC‐TSD) [23], and MEKC [24]. Immunoassay methods are rapid and accurate [25] but their reagents are more expensive [2].…”
Section: Introductionmentioning
confidence: 99%
“…Sample preparation methods increase the sensitivity of the assay by preconcentration and also increase specificity by removing the majority of the matrix interferents. Dispersive liquid–liquid microextraction [11,26], dispersive microsolid phase extraction [12], MEPS [13], molecularly imprinted solid phase microextraction [15], solidified floating organic drop microextraction [16], SPE [17,19,27], and solid‐phase microextraction (SPME) [18,23] are the main sample preparation methods which are used to extract PHT from plasma [8,9,12–14,16,18], urine [11,12,14,16,19], exhaled breath condensate (EBC) [5], dried blood spot [28–30], and dried saliva spot [31] samples. Although these methods are efficient, they have several drawbacks, such as high and boring steps and organic solvent consumption in dispersive liquid–liquid microextraction, dispersive microsolid phase extraction, and microextraction by packed sorbent [32,33], and high cost of commercial SPME fibers and long extraction times in SPME [34].…”
Section: Introductionmentioning
confidence: 99%
“…LPME as a miniaturized application of LLE has rapid, low cost, and simple procedure. LPME has several modes including single drop microextraction , hollow fiber LPME , dispersive liquid‐phase microextraction (DLPME) , and solidified floating organic drop (SFOD) microextraction .…”
Section: Introductionmentioning
confidence: 99%